2011
DOI: 10.1016/j.compstruct.2010.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Crushing and energy absorption performance of different geometrical shapes of small-scale glass/polyester composite tubes under quasi-static loading conditions

Abstract: This paper presents the quasi-static crushing performance of nine different geometrical shapes of small-scale composite tubes. The idea is to understand the effect of geometry, dimension and triggering mechanism on the progressive deformation of small-scale composite tubes. Different geometrical shapes of the composite tubes have been manufactured by hand lay-up technique using uni-directional E-glass fabric (with single and double plies) and polyester resin. Dedicated quasi-static tests (144 tests) have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 29 publications
6
54
0
Order By: Relevance
“…6a. These are consistent with the findings by Palanivelu et al [23] and Chiu et al [24]. In the 0˚ plies, the main forms of failure are ply splitting and brittle fibre fracture via bending or shearing.…”
Section: Typical Damage Modessupporting
confidence: 82%
“…6a. These are consistent with the findings by Palanivelu et al [23] and Chiu et al [24]. In the 0˚ plies, the main forms of failure are ply splitting and brittle fibre fracture via bending or shearing.…”
Section: Typical Damage Modessupporting
confidence: 82%
“…Other investigations were reported on the effect of triggering of different cross-sectional shapes. It is reported that under quasi-static axial crushing the peak load is at maximum with edge triggering at 45˚ compared to 90˚ tulip triggering [45]. However, tulip triggering showed higher specific energy absorption for all cross section tubes tested than edge triggered.…”
Section: Trigger Mechanismmentioning
confidence: 98%
“…Palanivelu et al [45] In summary circular shapes geometry have outstanding performance compared to other geometry shapes tested. Moreover, compared to other shapes apart from radial corrugated circular, circular shapes geometry absorbs most of axial crushing energy.…”
Section: Structural Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Damage and fracture in a composite laminate are complex phenomena [2], with a multitude of interacting mechanisms which affect the final response [3][4][5][6][7]. The ability to accurately predict the initiation and progression of damage in a structure through finite element modelling, is highly advantageous in the design process for composite structures by reducing the need for expensive and time-consuming subcomponent testing [1].…”
Section: Introductionmentioning
confidence: 99%